If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = -2(x + 3) + -5 Multiply F * x xF = -2(x + 3) + -5 Reorder the terms: xF = -2(3 + x) + -5 xF = (3 * -2 + x * -2) + -5 xF = (-6 + -2x) + -5 Reorder the terms: xF = -6 + -5 + -2x Combine like terms: -6 + -5 = -11 xF = -11 + -2x Solving xF = -11 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2x + xF = -11 + -2x + 2x Combine like terms: -2x + 2x = 0 2x + xF = -11 + 0 2x + xF = -11 Reorder the terms: 11 + 2x + xF = -11 + 11 Combine like terms: -11 + 11 = 0 11 + 2x + xF = 0 The solution to this equation could not be determined.
| (2a^2-1)(8a-5)= | | 0.6+a=1.3 | | 10=.25(b-11) | | X(15x+11)+2=0 | | 4y-10=2y+5 | | 4x-9=-6+5x | | -4.9t^2+24.5t+2=0 | | 7x+3x-4x=3-3(x+4) | | 139=-5-2(4+8P) | | (5x^3y^2-3xy^5+12x^2)-(-9x^2-8x^3y^2+2xy^5)=0 | | 4x-9=-6+-5x | | 3x(-3)+b= | | 7-3a=11+a | | X(15x+11x)+2=0 | | 4.9t^2-24.5t+2=0 | | c^2-3c-18= | | 6+3(13-2)-25= | | 5x+2-4x=5+8 | | -5y+7y=10 | | 2(4p+3)-3(3p-6)-16p= | | -6(7x-1)=-8x+9(-3x+4) | | .5(4m+5)=-6 | | t^2-24.5t+2=0 | | 2a/3a-3/4=3a/4a | | h(t)=-16t^2+20t+4 | | 7+3a=11-a | | 3(4x-6)=2(4x-3)-(x+8) | | 13.04=f+8.25 | | 9n-3n= | | 13(t+1)-3(2+4t)=48 | | 180=(9x+4)-y | | -15=-5t^2+30t |